2014 IEEE Symposium on Foundations of Computational Intelligence (FOCI) 2014
DOI: 10.1109/foci.2014.7007805
|View full text |Cite
|
Sign up to set email alerts
|

Test problems and representations for graph evolution

Abstract: Graph evolution -evolving a graph or network to fit specific criteria -is a recent enterprise because of the difficulty of representing a graph in an easily evolvable form. Simple, obvious representations such as adjacency matrices can prove to be very hard to evolve and some easy-to-evolve representations place severe limits on the space of graphs that is explored. This study fills in a gap in the literature by presenting two scalable families of benchmark functions. These functions are tested on a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…An earlier study [3], defined a collection of test problems for graph evolution. These include the simple unimodal edgemax problem, network stability problems, and finding graphs that are difficult to color properly.…”
Section: Other Graph-evolution Problemsmentioning
confidence: 99%
“…An earlier study [3], defined a collection of test problems for graph evolution. These include the simple unimodal edgemax problem, network stability problems, and finding graphs that are difficult to color properly.…”
Section: Other Graph-evolution Problemsmentioning
confidence: 99%
“…This graph was chosen because earlier research [3], [5] has demonstrated that graphs having vertices with degree 4-5 are desirable for the test problems. Other work on network evolution appears in [1]- [4], [6].…”
Section: Profile Matching (Pm) Problemmentioning
confidence: 99%
“…This graph was chosen because previous research [5], [7] has demonstrated that graphs having vertices with four or five edges are desirable for the test problems. Other graph topologies appear in previous work [1], [3], [5], [6], [8].…”
Section: The Local Thads-n Representationmentioning
confidence: 99%